Photovoltaic glass and preparation method and application thereof

By using a combination of silica-alginate and alumina-alginate transmissive layers on photovoltaic glass, the problem of low adhesion and strength of the existing photovoltaic glass coating technology is solved, and the effect of improving transmittance and enhancing adhesion and strength is achieved.

CN119912176APending Publication Date: 2025-05-02HEBEI GUANGXING SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993387.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Although the existing photovoltaic glass coating technology can improve the transmittance of glass, its adhesion and strength are not high, and it is prone to scratches and damage.

Method used

The main transmissive layer including the silica-alginate transmissive layer and the alumina-alginate transmissive layer is adopted to improve the transmittance of the photovoltaic glass while enhancing the strength and adhesion of the urge film through the coordination of the silica-alginate transmissive layer and the alumina-alginate transmissive layer.

Benefits of technology

It effectively improves the transmittance of photovoltaic glass, while also enhancing the strength and adhesion of the urgency film, solving the problem that the coating is prone to scratches and damage in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912176A_ABST
    Figure CN119912176A_ABST
Patent Text Reader

Abstract

The invention provides photovoltaic glass as well as a preparation method and application thereof. The photovoltaic glass comprises a glass main body (1), and a main anti-reflection layer (2); wherein the main anti-reflection layer (2) is arranged on the surface of the glass main body (1), and the main anti-reflection layer (2) comprises a silicon dioxide-alginate anti-reflection layer (21) and an aluminum oxide-alginate anti-reflection layer (22). The preparation method comprises the step of coating the silicon dioxide-alginate coating liquid and the aluminum oxide-alginate coating liquid on the surface of the glass main body (1) in any sequence. According to the photovoltaic glass, the transmittance of the photovoltaic glass can be improved, meanwhile, the strength and the adhesive force of the anti-reflection layer can be improved, and the photovoltaic glass has a remarkable market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of photovoltaic glass, and in particular to photovoltaic glass and a preparation method and application thereof. Background Art

[0002] Traditional non-renewable energy sources such as coal and oil are gradually being consumed, and the use of traditional energy has caused great harm to the environment. Solar energy is inexhaustible, and as a clean and renewable energy source that can replace traditional energy sources, it has attracted more and more attention. According to the way of energy conversion, the use of solar energy can be divided into photothermal conversion and photoelectric conversion. For example, the applications of photothermal conversion include solar water heaters, solar stoves, solar thermal power generation systems, etc.; the applications of photoelectric conversion include solar panels, solar cars, solar boats, etc.

[0003] Photovoltaic glass, as an inorganic material used for solar photovoltaic conversion packaging, has a transmittance that directly affects the photovoltaic conversion efficiency of photovoltaic devices. In order to obtain photovoltaic glass with higher transmittance, the production method is often adjusted by reducing the iron content introduced in each process, thereby reducing the chromaticity of photovoltaic glass and improving its transmittance; glass embossing can also be used to reduce the reflection effect of light and thereby improve the transmittance of light. However, the transmittance of the photovoltaic glass produced still needs to be improved.

[0004] At present, for finished photovoltaic glass, post-processing treatment of surface coating can more directly improve the transmittance of glass. Commonly used coating liquids include inorganic deposition films such as silicon dioxide, titanium dioxide, and niobium pentoxide. Although these coatings can improve the transmittance of glass, their adhesion and strength are not high, and the coatings are easily scratched and damaged.

[0005] Therefore, there is an urgent need to provide a photovoltaic glass anti-reflection film that can improve the transmittance of the photovoltaic glass while also improving the strength and adhesion of the anti-reflection film. Summary of the invention

[0007] A technical problem to be solved by the present disclosure is that although coating photovoltaic glass can improve the transmittance of the glass, its adhesion and strength are not high.

[0008] To solve the above technical problems, in the first aspect, an embodiment of the present disclosure provides a photovoltaic glass, including a glass body; and a main anti-reflection layer; wherein the main anti-reflection layer is arranged on the surface of the glass body, and the main anti-reflection layer includes a silica-alginate anti-reflection layer and an aluminum oxide-alginate anti-reflection layer.

[0009] In some embodiments, the silica-alginate anti-reflection layer is located between the alumina-alginate anti-reflection layer and the glass body.

[0010] In some embodiments, the alginate is sodium alginate and / or potassium alginate.

[0011] In some embodiments, the weight ratio of silica to alginate in the silica-alginate anti-reflection layer is 1:0.6-1.5; the weight ratio of alumina to alginate in the alumina-alginate anti-reflection layer is 1:1.5-3.

[0012] In some embodiments, the thickness of the silica-alginate anti-reflection layer is 50-90 nm, and the thickness of the alumina-alginate anti-reflection layer is 25-50 nm.

[0013] In some embodiments, the photovoltaic glass further includes an anti-reflection layer, which includes a first inorganic fluorine compound-alginate anti-reflection layer disposed between the glass body and the main anti-reflection layer and a second inorganic fluorine compound-alginate anti-reflection layer disposed on the side of the main anti-reflection layer away from the glass body.

[0014] In some embodiments, the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride; in some embodiments, the inorganic fluorine compound is magnesium fluoride.

[0015] In some embodiments, the weight ratio of the inorganic fluorine compound to alginate in the first inorganic fluorine compound-alginate anti-reflection layer and the second inorganic fluorine compound-alginate anti-reflection layer is independently 1:0.6-1.

[0016] In some embodiments, the thickness of the first inorganic fluorine compound-alginate anti-reflection layer and the second inorganic fluorine compound-alginate anti-reflection layer are each independently 120-200 nm.

[0017] In some embodiments, the first inorganic fluorine compound-alginate anti-reflection layer and the second inorganic fluorine compound-alginate anti-reflection layer have the same thickness.

[0018] In a second aspect, an embodiment of the present disclosure provides a method for preparing photovoltaic glass, comprising the following steps: coating a silica-alginate coating liquid and an aluminum oxide-alginate coating liquid on a surface of a glass body in any order.

[0019] In some embodiments, the silica-alginate coating liquid and the aluminum oxide-alginate coating liquid are sequentially coated on the surface of the glass body.

[0020] In some embodiments, the alginate is sodium alginate and / or potassium alginate.

[0021] In some embodiments, the method includes the following steps: sequentially coating a first inorganic fluorine compound-alginate coating liquid, a silicon dioxide-alginate coating liquid, an aluminum oxide-alginate coating liquid, and a second inorganic fluorine compound-alginate coating liquid onto the surface of the glass body.

[0022] In some embodiments, the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride; in some embodiments, the inorganic fluorine compound is magnesium fluoride.

[0023] In some embodiments, the coating is performed by dipping; the coating conditions include at least: an ultrasonic frequency of 50-200 Hz, a temperature of 40-60° C., a rotation speed of 200-300 rpm, and a time of 20-100 min.

[0024] In some embodiments, the coating time of the first inorganic fluorine compound-alginate coating solution and the coating time of the second inorganic fluorine compound-alginate coating solution are the same.

[0025] In some embodiments, the silica-alginate coating liquid, the alumina-alginate coating liquid, the first inorganic fluorine compound-alginate and the second inorganic fluorine compound-alginate coating liquid each independently further contain a crosslinking agent, and the crosslinking agent is selected from at least one of epichlorohydrin, boric acid and ethylene glycol diglycidyl ether.

[0026] In some embodiments, the concentration of silica in the silica-alginate coating liquid is 20-50 g / L, and the weight ratio of silica to alginate is 1:0.6-1.5; the concentration of alumina in the alumina-alginate coating liquid is 15-25 g / L, and the weight ratio of alumina to alginate is 1:1.5-3; the concentrations of the inorganic fluorine compound in the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid are each independently 40-60 g / L, and the weight ratio of the inorganic fluorine compound to alginate is each independently 1:0.6-1.

[0027] In a third aspect, an embodiment of the present disclosure provides an application of the photovoltaic glass provided in the second aspect or the photovoltaic glass obtained by the preparation method provided in the second aspect in a solar cell.

[0028] Through the above technical scheme, the photovoltaic glass provided by the present invention is provided with a main transmittance-enhancing layer on the surface of the glass body, and the main transmittance-enhancing layer includes a silica-alginate transmittance-enhancing layer and an alumina-alginate transmittance-enhancing layer. Through the coordinated effect of the silica-alginate transmittance-enhancing layer and the alumina-alginate transmittance-enhancing layer, the transmittance of the photovoltaic glass can be improved while the strength and adhesion of the transmittance-enhancing layer can be improved, and thus the photovoltaic glass has significant market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present disclosure or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 It is a schematic diagram of the structure of the photovoltaic glass disclosed in the embodiment of the present disclosure.

[0031] Description of reference numerals:

[0032] 1. Glass body; 2. Main transmittance-enhancing layer; 21. Silica-alginate transmittance-enhancing layer; 22. Alumina-alginate transmittance-enhancing layer; 3. Auxiliary transmittance-enhancing layer; 31. First inorganic fluorine compound-alginate transmittance-enhancing layer; 32. Second inorganic fluorine compound-alginate transmittance-enhancing layer. DETAILED DESCRIPTION

[0033] The following is a further detailed description of the embodiments of the present disclosure in conjunction with the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to exemplarily illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure. The present disclosure can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

[0034] The present disclosure provides these embodiments to make the present disclosure thorough and complete, and to fully express the scope of the present disclosure to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values ​​set forth in these embodiments should be interpreted as being merely exemplary, and not as limiting.

[0035] It should be noted that, in the description of the present disclosure, unless otherwise specified, the meaning of "multiple" is greater than or equal to two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating the orientation or positional relationship, are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present disclosure. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.

[0036] In addition, the words "first", "second" and similar words used in the present disclosure do not indicate any order, quantity or importance, but are only used to distinguish different parts. "Vertical" does not mean vertical in the strict sense, but is within the tolerance range. "Parallel" does not mean parallel in the strict sense, but is within the tolerance range. "Include" or "comprising" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0037] It should also be noted that in the description of the present disclosure, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present disclosure can be understood according to the specific circumstances. When a specific device is described as being located between a first device and a second device, there may or may not be an intermediate device between the specific device and the first device or the second device.

[0038] All terms used in the present disclosure have the same meanings as those understood by those of ordinary skill in the art to which the present disclosure belongs, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an idealized or extremely formal sense, unless explicitly defined as such herein.

[0039] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.

[0040] In a first aspect, the present disclosure provides a photovoltaic glass, see Figure 1 , comprising a glass body 1; and a main anti-reflection layer 2; wherein the main anti-reflection layer 2 is arranged on the surface of the glass body 1, and the main anti-reflection layer 2 comprises a silica-alginate anti-reflection layer 21 and an aluminum oxide-alginate anti-reflection layer 22.

[0041] During the research process, the inventors of the present invention unexpectedly discovered that the photovoltaic glass is provided with a main transmittance-enhancing layer 2 on the surface of the glass body 1, and the main transmittance-enhancing layer 2 includes a silica-alginate transmittance-enhancing layer 21 and an alumina-alginate transmittance-enhancing layer 22. Through the coordinated effect of the silica-alginate transmittance-enhancing layer 21 and the alumina-alginate transmittance-enhancing layer 22, the transmittance of the photovoltaic glass can be improved while the strength and adhesion of the transmittance-enhancing layer can be improved, which has a significant market prospect.

[0042] According to the present disclosure, the main anti-reflection layer 2 is arranged on the surface of the glass body 1 . The main anti-reflection layer 2 can be arranged on the surface of one side of the glass body 1 , or on the surfaces of both sides of the glass body 1 .

[0043] According to the present disclosure, the silica-alginate anti-reflection layer 21 and the alumina-alginate anti-reflection layer 22 are arranged along the thickness direction of the main anti-reflection layer 2. There is no particular limitation on the arrangement order of the silica-alginate anti-reflection layer 21 and the alumina-alginate anti-reflection layer 22 on the surface of the glass body 1. The silica-alginate anti-reflection layer 21 may be located between the glass body 1 and the alumina-alginate anti-reflection layer 22, or the alumina-alginate anti-reflection layer 22 may be located between the glass body 1 and the silica-alginate anti-reflection layer 21. In order to further improve the strength and adhesion of the anti-reflection layer while improving the transmittance of the photovoltaic glass, in some embodiments, the silica-alginate anti-reflection layer is located between the alumina-alginate anti-reflection layer and the glass body.

[0044] According to the present disclosure, in some embodiments, the alginate is sodium alginate and / or potassium alginate. The inventors found that in the above embodiments, the alginate can improve the dispersion of silicon dioxide in the silicon dioxide-alginate anti-reflection layer 21, and can also improve the dispersion of aluminum oxide in the aluminum oxide-alginate anti-reflection layer 22, thereby improving the transmittance of the photovoltaic glass.

[0045] According to the present disclosure, in order to further improve the strength and adhesion of the anti-reflection layer while improving the transmittance of the photovoltaic glass, in some embodiments, the weight ratio of silica to alginate in the silica-alginate anti-reflection layer 21 is 1:0.6-1.5, specifically 1:0.6, 1:0.9, 1:1.2, 1:1.5, or any value between the above two values; the weight ratio of alumina to alginate in the alumina-alginate anti-reflection layer 22 is 1:1.5-3, specifically 1:1.5, 1:2, 1:2.5, 1:3, or any value between the above two values.

[0046] According to the present disclosure, the thickness of the silica-alginate anti-reflection layer 21 and the alumina-alginate anti-reflection layer 22 can be conventional choices in the art. In order to further improve the transmittance of the photovoltaic glass, in some embodiments, the thickness of the silica-alginate anti-reflection layer 21 is 50-90nm, specifically 50nm, 70nm, 90nm, or any value between the above two values; the thickness of the alumina-alginate anti-reflection layer 22 is 25-50nm, specifically 25nm, 40nm, 50nm, or any value between the above two values.

[0047] According to the present disclosure, in some embodiments, the photovoltaic glass further includes an anti-reflection layer 3, which includes a first inorganic fluorine compound-alginate anti-reflection layer 31 disposed between the glass body and the main anti-reflection layer and a second inorganic fluorine compound-alginate anti-reflection layer 32 disposed on the side of the main anti-reflection layer away from the glass body. The inventors found that in the above embodiments, through the synergistic effect of the anti-reflection layer 3 and the main anti-reflection layer 2, the transmittance of the photovoltaic glass can be further improved while the strength and adhesion of the anti-reflection layer can be improved.

[0048] According to the present disclosure, the inorganic fluorine compound can be an inorganic fluorine compound conventionally selected in the art. In order to further improve the transmittance of photovoltaic glass, in some embodiments, the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride, preferably magnesium fluoride.

[0049] According to the present disclosure, in some embodiments, the weight ratio of the inorganic fluorine compound to alginate in the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32 is independently 1:0.6-1, specifically 1:0.6, 1:0.8, 1:1, or any value between the two aforementioned values.

[0050] According to the present disclosure, in order to further improve the transmittance of photovoltaic glass, in some embodiments, the thickness of the first inorganic fluorine compound-alginate transmittance-enhancing layer and the second inorganic fluorine compound-alginate transmittance-enhancing layer are each independently 120-200nm, specifically 120nm, 140nm, 160nm, 180nm, 200nm, or any value between the above two values.

[0051] According to the present disclosure, in some embodiments, the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32 have the same thickness. The inventors found that in the above embodiments, through the cooperation between the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32, the superposition of the incident light on the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32 can achieve reflection cancellation, thereby further improving the transmittance of the photovoltaic glass.

[0052] In a second aspect, an embodiment of the present disclosure provides a method for preparing the above-mentioned photovoltaic glass, comprising the following steps: coating a silica-alginate coating liquid and an aluminum oxide-alginate coating liquid on the surface of the glass body 1 in any order.

[0053] According to the present disclosure, the process flow of the photovoltaic glass is simple, easy to operate, and suitable for industrial production.

[0054] According to the present disclosure, the silica-alginate coating liquid and the alumina-alginate coating liquid can be sequentially coated on the surface of the glass body 1, or the alumina-alginate coating liquid and the silica-alginate coating liquid can be sequentially coated on the surface of the glass body 1. In order to further improve the strength and adhesion of the anti-reflection layer while improving the transmittance of the photovoltaic glass, in some embodiments, the silica-alginate coating liquid and the alumina-alginate coating liquid are sequentially coated on the surface of the glass body 1.

[0055] According to the present disclosure, the alginate can be a conventionally selected alginate in the art, for example, sodium alginate, potassium alginate, calcium alginate, ammonium alginate, etc. In some embodiments, the alginate is sodium alginate and / or potassium alginate. The inventors found that in the above embodiments, the alginate can improve the dispersion of silicon dioxide in the silicon dioxide-alginate coating liquid, and can also improve the dispersion of aluminum oxide in the aluminum oxide-alginate coating liquid, thereby improving the transmittance of the photovoltaic glass.

[0056] According to the present disclosure, in some embodiments, the method includes the following steps: sequentially coating a first inorganic fluorine compound-alginate coating liquid, a silicon dioxide-alginate coating liquid, an aluminum oxide-alginate coating liquid, and a second inorganic fluorine compound-alginate coating liquid on the surface of the glass body. The inventors found that, see Figure 1 In the above embodiment, a first inorganic fluoride-alginate anti-reflection layer 31, a silica-alginate anti-reflection layer 21, an aluminum oxide-alginate anti-reflection layer 22 and a second inorganic fluoride compound-alginate anti-reflection layer 32 can be formed in sequence on the surface of the glass body 1 along the direction away from the glass body 1. Through the synergistic effect between the above four anti-reflection layers, the transmittance of the photovoltaic glass can be further improved while the strength and adhesion of the anti-reflection layers can be improved.

[0057] According to the present disclosure, the inorganic fluorine compound can be an inorganic fluorine compound conventionally selected in the art. In order to further improve the transmittance of photovoltaic glass, in some embodiments, the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride, preferably magnesium fluoride.

[0058] According to the present disclosure, there is no particular limitation on the coating method, which can be a common coating method in the art, such as dipping, spraying, curtain coating, pulling, roller coating, etc. In some embodiments, the coating is carried out by dipping; the coating conditions at least include: the ultrasonic frequency is 50-200Hz, specifically 50Hz, 100Hz, 150Hz, 200Hz, or any value between the above two values; the temperature is 40-60℃, specifically 40℃, 50℃, 60℃, or any value between the above two values; the rotation speed is 200-300rpm, specifically 200rpm, 250rpm, 300rpm, or any value between the above two values; the time is 20-100min, specifically 20min, 40min, 60min, 80min, 100min, or any value between the above two values.

[0059] According to the present disclosure, in order to further improve the transmittance of photovoltaic glass, in some embodiments, the coating time of the silica-alginate coating liquid is 20-30 min, specifically 20 min, 25 min, 30 min, or any value between the aforementioned two values; the coating time of the aluminum oxide-alginate coating liquid is 40-60 min, specifically 40 min, 50 min, 60 min, or any value between the aforementioned two values; the coating time of the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid are each independently 80-100 min, specifically 80 min, 90 min, 100 min, or any value between the aforementioned two values.

[0060] According to the present disclosure, the coating time of the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid may be the same or different. In some embodiments, the coating time of the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid is the same. The inventors found that in the above-mentioned embodiments, the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32 formed by controlling the coating time of the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid can make the superposition of the reflected light of the incident light on the first inorganic fluorine compound-alginate anti-reflection layer 31 and the second inorganic fluorine compound-alginate anti-reflection layer 32 realize reflection cancellation, thereby further improving the transmittance of the photovoltaic glass.

[0061] According to the present disclosure, in some embodiments, the silica-alginate coating liquid, the alumina-alginate coating liquid, the first inorganic fluorine compound-alginate and the second inorganic fluorine compound-alginate coating liquid each independently further contain a cross-linking agent, and the cross-linking agent is selected from at least one of epichlorohydrin, boric acid and ethylene glycol diglycidyl ether. The inventors found that in the above embodiments, adding a cross-linking agent to each coating liquid can improve the stability and transmittance of the corresponding anti-reflection layer.

[0062] According to the present disclosure, the amount of the crosslinking agent can be the amount conventionally selected in the art. In some embodiments, the weight ratio of the crosslinking agent to alginate is 0.05-0.2:1, specifically 0.05:1, 0.1:1, 0.2:1, or any value between the foregoing two values.

[0063] According to the present disclosure, in some embodiments, the concentration of silicon dioxide in the silicon dioxide-alginate coating liquid is 20-50 g / L, specifically 20 g / L, 30 g / L, 40 g / L, 50 g / L, or any value between the foregoing two values; the weight ratio of silicon dioxide to alginate is 1:0.6-1.5, specifically 1:0.6, 1:0.9, 1:1.3, 1:1.2, 1:1.5, or any value between the foregoing two values; the concentration of aluminum oxide in the aluminum oxide-alginate coating liquid is 15-25 g / L, specifically 15 g / L, 20 g / L, 25 g / L, or any value between the foregoing two values. The weight ratio of alumina to alginate is 1:1.5-3, specifically 1:1.5, 1:2, 1:2.5, 1:3, or any value between the aforementioned two values; the concentrations of the inorganic fluorine compound in the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid are each independently 40-60 g / L, specifically 40 g / L, 50 g / L, 60 g / L, or any value between the aforementioned two values; the weight ratio of the inorganic fluorine compound to alginate is each independently 1:0.6-1, specifically 1:0.6, 1:0.8, 1:1, or any value between the aforementioned two values.

[0064] According to the present disclosure, in the process of preparing a silica-alginate coating liquid, an alumina-alginate coating liquid, a first inorganic fluorine compound-alginate and a second inorganic fluorine compound-alginate coating liquid, alginate is first mixed with water at a temperature of 60-80°C for 30-60 minutes, and then silica (or alumina, a first inorganic fluorine compound, a second inorganic fluorine compound) is added and mixed at a temperature of 60-80°C for 1-2 hours.

[0065] According to the present disclosure, after the glass body 1 is coated in the corresponding coating liquid, it needs to be cured before coating with other coating liquids. The curing method can be a conventional curing method selected in the art. In some embodiments, the curing includes thermal curing and photocuring. The thermal curing conditions include at least: a temperature of 150-180°C, specifically 150°C, 160°C, 170°C, 180°C, or any value between the above two values; the photocuring conditions include at least: an ultraviolet intensity of 300-600mW / cm 2 , specifically 300mW / cm 2 , 400mW / cm 2 , 500mW / cm 2 ,

[0066] 600mW / cm 2 , or any value between the above two values.

[0067] According to a particularly preferred embodiment of the present disclosure, a method for preparing photovoltaic glass is provided, comprising the following steps: applying a first inorganic fluorine compound-alginate coating liquid, a silicon dioxide-alginate coating liquid, an aluminum oxide-alginate coating liquid, and a second inorganic fluorine compound-alginate coating liquid to the surface of a glass body 1 in sequence;

[0068] The alginate is sodium alginate and / or potassium alginate; the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride, preferably magnesium fluoride; the silica-alginate coating liquid, the alumina-alginate coating liquid, the first inorganic fluorine compound-alginate and the second inorganic fluorine compound-alginate coating liquid each independently further contain a crosslinking agent, the crosslinking agent is selected from at least one of epichlorohydrin, boric acid and ethylene glycol diglycidyl ether; the concentration of silica in the silica-alginate coating liquid is 20-50 g / L, and the weight ratio of silica to alginate is 1:0.6-1.5; the concentration of alumina in the alumina-alginate coating liquid is 15 -25g / L, the weight ratio of alumina to alginate is 1:1.5-3; the concentrations of inorganic fluorine compounds in the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid are each independently 40-60g / L, and the weight ratios of inorganic fluorine compounds to alginate are each independently 1:0.6-1; the coating is carried out in the form of dipping; the coating conditions include at least: an ultrasonic frequency of 50-200Hz, a temperature of 40-60°C, a rotation speed of 200-300rpm, and a time of 20-100min; the coating time of the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid is the same.

[0069] Under the above particularly preferred implementation mode, the prepared photovoltaic glass can improve the transmittance of the photovoltaic glass while also improving the strength and adhesion of the anti-reflection layer, and has a significant market prospect.

[0070] In a third aspect, an embodiment of the present disclosure provides an application of the photovoltaic glass provided in the second aspect or the photovoltaic glass obtained by the preparation method provided in the second aspect in a solar cell.

[0071] The present disclosure will be described in detail below through examples.

[0072] In the following examples, nano silicon dioxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model S104597; nano aluminum oxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model A396574; nano magnesium fluoride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model M108388; epichlorohydrin was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model E108182; unless otherwise specified, other raw materials are commercially available.

[0073] Example 1

[0074] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100 g of pure water was used as the base. Pour 100 g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 70 °C. 3.3 g of sodium alginate was added and stirred for 40 min until the sodium alginate was completely dissolved and clarified. Then, 2.3 g of nano-SiO was added to the sodium alginate solution. 2 , while maintaining the temperature at 70°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 3.3 g of sodium alginate and 1.8 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 3.3 g of sodium alginate and 4 g of nano-magnesium fluoride);

[0075] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.2 g of crosslinking agent epichlorohydrin was added to the mixed solution, sodium alginate / nano-alumina mixed solution, and sodium alginate / nano-magnesium fluoride mixed solution, respectively, and stirred at 70 ° C for 3 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid, sodium alginate / nano-magnesium fluoride coating liquid;

[0076] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 80 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The coating liquid (coating time is 40 minutes), the sodium alginate / nano-alumina coating liquid (coating time is 20 minutes), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time is 80 minutes) are used to obtain photovoltaic glass.

[0077] The schematic diagram of the structure of the photovoltaic glass obtained in Example 1 is shown in Figure 1 .

[0078] Example 2

[0079] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100 g of pure water was used as the base. Pour 100 g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 60 °C. 4.2 g of sodium alginate was added and stirred for 30 min until the sodium alginate was completely dissolved and clarified. Then, 3 g of nano-SiO was added to the sodium alginate solution. 2 , while maintaining the temperature at 60°C, continue magnetic stirring for 1 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 4.2 g of sodium alginate and 1.5 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 4.2 g of sodium alginate and 4.5 g of nano-magnesium fluoride);

[0080] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.3 g of boric acid as a crosslinking agent was added to the mixed solution, sodium alginate / nano-alumina mixed solution, and sodium alginate / nano-magnesium fluoride mixed solution, respectively, and stirred at 60 °C for 2 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid, sodium alginate / nano-magnesium fluoride coating liquid;

[0081] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 200 Hz, a temperature of 40°C, and a rotation speed of 200 rpm for 85 min. The glass surface was then thermally cured at a temperature of 150°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 300 W / cm 2Light curing for 8 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The photovoltaic glass was obtained by mixing the coating liquid (coating time was 45 min), the sodium alginate / nano-alumina coating liquid (coating time was 22 min), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time was 85 min).

[0082] Example 3

[0083] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100 g of pure water was used as the base. Pour 100 g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 60 °C. 2.6 g of sodium alginate was added and stirred for 50 min until the sodium alginate was completely dissolved and clarified. Then, 4.2 g of nano-SiO was added to the sodium alginate solution. 2 , while maintaining the temperature at 80°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 2.6 g of sodium alginate and 2.4 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 2.6 g of sodium alginate and 4.2 g of nano-magnesium fluoride);

[0084] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.4 g of crosslinking agent epichlorohydrin was added to the mixed solution, sodium alginate / nano-alumina mixed solution, and sodium alginate / nano-magnesium fluoride mixed solution, respectively, and stirred at 80 ° C for 4 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid, sodium alginate / nano-magnesium fluoride coating liquid;

[0085] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dipped on the glass surface at an ultrasonic frequency of 50 Hz, a temperature of 60°C, and a rotation speed of 300 rpm for 90 min. The glass surface was thermally cured at a temperature of 180°C for 1 h. The glass surface was then exposed to ultraviolet light at an intensity of 600 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The photovoltaic glass was obtained by mixing the coating liquid (coating time was 50 min), the sodium alginate / nano-alumina coating liquid (coating time was 24 min), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time was 90 min).

[0086] Example 4

[0087] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100 g of pure water was used as the base. Pour 100 g of pure water into a beaker and stir it in a magnetic stirrer at a temperature of 70 °C. 4.5 g of sodium alginate was added and stirred for 40 min until the sodium alginate was completely dissolved and clarified. Then, 3.5 g of nano-SiO was added to the sodium alginate solution. 2 , while maintaining the temperature at 70°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 4.5 g of sodium alginate and 1.6 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 4.5 g of sodium alginate and 5.2 g of nano-magnesium fluoride);

[0088] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.6 g of crosslinking agent epichlorohydrin was added to the mixed solution, sodium alginate / nano-alumina mixed solution, and sodium alginate / nano-magnesium fluoride mixed solution, respectively, and stirred at 70 ° C for 3 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid, sodium alginate / nano-magnesium fluoride coating liquid;

[0089] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dipped on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 95 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The photovoltaic glass was obtained by mixing the coating liquid (coating time was 55 min), the sodium alginate / nano-alumina coating liquid (coating time was 26 min), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time was 95 min).

[0090] Example 5

[0091] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100g of pure water was used as the base. Pour 100g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 70°C. 5g of sodium alginate was added and stirred for 40min until the sodium alginate was completely dissolved and clarified. Then, 5g of nano-SiO2 was added to the sodium alginate solution. 2 , while maintaining the temperature at 70°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 5 g of sodium alginate and 2.1 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 5 g of sodium alginate and 5.8 g of nano-magnesium fluoride);

[0092] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.8 g of crosslinking agent epichlorohydrin was added to the mixed solution, sodium alginate / nano-alumina mixed solution, and sodium alginate / nano-magnesium fluoride mixed solution, respectively, and stirred at 70 ° C for 3 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid, sodium alginate / nano-magnesium fluoride coating liquid;

[0093] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dipped on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 100 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The photovoltaic glass was obtained by mixing the coating liquid (coating time was 60 min), the sodium alginate / nano-alumina coating liquid (coating time was 30 min), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time was 100 min).

[0094] Example 6

[0095] Photovoltaic glass was prepared according to the method of Example 1, except that step (3) was replaced by:

[0096] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 80 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The photovoltaic glass was obtained by mixing the coating liquid (coating time was 40 min), the sodium alginate / nano-alumina coating liquid (coating time was 20 min), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time was 100 min).

[0097] Example 7

[0098] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100g of pure water was used as the base. Pour 100g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 70°C. 3.3g of sodium alginate was added and stirred for 40min until the sodium alginate was completely dissolved and clarified. Then, 2.3g of nano-SiO 2 , while maintaining the temperature at 70°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, respectively prepare a sodium alginate / nano-alumina mixed solution (including 3.3 g of sodium alginate and 1.8 g of nano-alumina) and a sodium alginate / nano-magnesium fluoride mixed solution (including 3.3 g of sodium alginate and 4 g of nano-magnesium fluoride);

[0099] (2) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 80 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat sodium alginate / nano-SiO on the glass surface 2 The coating liquid (coating time is 40 minutes), the sodium alginate / nano-alumina coating liquid (coating time is 20 minutes), and the sodium alginate / nano-magnesium fluoride coating liquid (coating time is 80 minutes) are used to obtain photovoltaic glass.

[0100] Example 8

[0101] Photovoltaic glass was prepared according to the method of Example 1, except that step (3) was replaced by:

[0102] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. The sodium alginate / nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 80 min. The glass surface was then thermally cured at a temperature of 160°C for 2 h. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 According to the above steps, the sodium alginate / nano-alumina coating liquid (coating time is 20 min), sodium alginate / nano-SiO 2 The coating liquid (coating time is 40 min) and the sodium alginate / nano-magnesium fluoride coating liquid (coating time is 80 min) are used to obtain photovoltaic glass.

[0103] Example 9

[0104] (1) Sodium alginate coordination treatment of nano-inorganic substances: 100 g of pure water was used as the base. Pour 100 g of pure water into a beaker and stir it in a magnetic stirrer. The temperature was controlled at 70 °C. 3.3 g of sodium alginate was added and stirred for 40 min until the sodium alginate was completely dissolved and clarified. Then, 2.3 g of nano-SiO was added to the sodium alginate solution. 2 , while maintaining the temperature at 70°C, continue magnetic stirring for 2 h to obtain sodium alginate / nano-SiO 2 Mixed solution; according to the above steps, prepare a sodium alginate / nano-alumina mixed solution (including 3.3 g sodium alginate and 1.8 g nano-alumina);

[0105] (2) Cross-linking modification of sodium alginate: The sodium alginate / nano-SiO obtained in step (1) 2 0.2 g of crosslinking agent epichlorohydrin was added to the mixed solution and the sodium alginate / nano-alumina mixed solution, respectively, and stirred at 70 °C for 3 h to obtain sodium alginate / nano-SiO 2 Coating liquid, sodium alginate / nano-alumina coating liquid;

[0106] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol to remove dust, oil stains, etc. on the glass surface. Sodium alginate / nano-SiO2 was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50 °C, and a rotation speed of 300 rpm. 2 After 40 minutes of coating, heat cure at 160°C for 2 hours, and then UV light at 400W / cm 2 According to the above steps, continue to dip-coat the sodium alginate / nano-alumina coating liquid on the glass surface (coating time is 20 minutes) to obtain photovoltaic glass.

[0107] Comparative Example

[0108] (1) Pour 100g of pure water into a beaker and add 2.3g of nano-SiO 2 , while maintaining the temperature at 70°C, magnetic stirring was performed for 2 h to obtain nano-SiO 2 Suspension; according to the above steps, respectively configure, nano alumina suspension (including 1.8g of nano alumina), nano magnesium fluoride suspension (including 4g of nano magnesium fluoride);

[0109] (2) The nano-SiO obtained in step (1) 2 0.2 g of crosslinking agent epichlorohydrin was added to the suspension, nano-alumina suspension, and nano-magnesium fluoride suspension, respectively, and stirred at 70 ° C for 3 h to obtain nano-SiO 2 Coating liquid, nano-alumina coating liquid, nano-magnesium fluoride coating liquid;

[0110] (3) Coating of glass surface film: The glass surface was cleaned with deionized water and alcohol respectively to remove dust, oil stains, etc. on the glass surface. Nano-magnesium fluoride coating liquid was dip-coated on the glass surface at an ultrasonic frequency of 100 Hz, a temperature of 50°C, and a rotation speed of 300 rpm for 80 minutes. The glass surface was then thermally cured at a temperature of 160°C for 2 hours. The glass surface was then exposed to ultraviolet light at an intensity of 400 W / cm 2 Light curing for 6 minutes; according to the above steps, continue to dip-coat the glass surface with nano-SiO 2 The coating liquid (coating time is 40 minutes), the nano-alumina coating liquid (coating time is 20 minutes), and the nano-magnesium fluoride coating liquid (coating time is 80 minutes) are used to obtain photovoltaic glass.

[0111] Test Example 1

[0112] The transmittance A of the photovoltaic glass prepared in Examples 1 to 9 and the comparative example was tested, and the results are shown in Table 1. The transmittance A of the photovoltaic glass was tested according to the method in the national standard "Test Method for Light Transmittance of Photovoltaic Glass Assemblies for Buildings" (GB / T 40415-2021).

[0113] The thicknesses of the silica-alginate anti-reflection layer 21, the aluminum oxide-alginate anti-reflection layer 22, the first inorganic fluorine compound anti-reflection layer 31, and the second inorganic fluorine compound anti-reflection layer 32 in the photovoltaic glass prepared in Examples 1 to 9 and the comparative example were tested, and the results are shown in Table 2.

[0114] Test Example 2

[0115] The transmittance B of the photovoltaic glass prepared in Examples 1 to 9 and the comparative example was tested, and the results are shown in Table 2. The test process of the transmittance B of the photovoltaic glass includes: grinding according to the wear resistance requirements in "GB / T18915.2-2013 Coated Glass Part 2: Low-E Coated Glass", and then performing a transmittance test according to the requirements in "GB / T 40415-2021 Test method for transmittance of photovoltaic glass assemblies for use in buildings".

[0116] Table 1

[0117]

[0118]

[0119] Table 2

[0120]

[0121] It can be seen from the results in Table 1 and Table 2 that, compared with the comparative example, the photovoltaic glass prepared by the method provided by the present invention in Examples 1 to 9 has a higher transmittance, and through the comparison of the transmittance A and the transmittance B, it can be seen that the transmittance of the photovoltaic glass prepared by the present invention does not change significantly after the surface is ground, indicating that the anti-reflection film has good strength and adhesion, and has significant market prospects.

[0122] So far, various embodiments of the present disclosure have been described in detail. In order to avoid obscuring the concept of the present disclosure, some details known in the art are not described. Based on the above description, those skilled in the art can fully understand how to implement the technical solution disclosed here.

[0123] Although some specific embodiments of the present disclosure have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present disclosure. It should be understood by those skilled in the art that the above embodiments may be modified or some technical features may be replaced by equivalents without departing from the scope and spirit of the present disclosure. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict.

Claims

1. A photovoltaic glass, characterized in that: include: Glass body (1); and Main anti-reflection layer (2); The main anti-reflection layer (2) is arranged on the surface of the glass body (1), and the main anti-reflection layer (2) comprises a silicon dioxide-alginate anti-reflection layer (21) and an aluminum oxide-alginate anti-reflection layer (22).

2. The photovoltaic glass according to claim 1, characterized in that: The silicon dioxide-alginate anti-reflection layer (21) is located between the aluminum oxide-alginate anti-reflection layer (22) and the glass body (1).

3. The photovoltaic glass according to claim 1, characterized in that: The alginate is sodium alginate and / or potassium alginate; Preferably, the weight ratio of silicon dioxide to alginate in the silicon dioxide-alginate anti-reflection layer (21) is 1:0.6-1.5; the weight ratio of aluminum oxide to alginate in the aluminum oxide-alginate anti-reflection layer (22) is 1:1.5-3; Preferably, the thickness of the silica-alginate anti-reflection layer (21) is 50-90 nm, and the thickness of the alumina-alginate anti-reflection layer (22) is 25-50 nm.

4. The photovoltaic glass according to any one of claims 1 to 3, characterized in that: The photovoltaic glass further comprises an anti-reflection layer (3), wherein the anti-reflection layer (3) comprises a first inorganic fluorine compound-alginate anti-reflection layer (31) arranged between the glass body (1) and the main anti-reflection layer (2), and a second inorganic fluorine compound-alginate anti-reflection layer (32) arranged on a side of the main anti-reflection layer (2) away from the glass body (1).

5. The photovoltaic glass according to claim 4, characterized in that: The inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride, preferably magnesium fluoride; Preferably, the weight ratio of the inorganic fluorine compound to the alginate in the first inorganic fluorine compound-alginate anti-reflection layer (31) and the second inorganic fluorine compound-alginate anti-reflection layer (32) is independently 1:0.6-1; Preferably, the thickness of the first inorganic fluorine compound-alginate anti-reflection layer (31) and the second inorganic fluorine compound-alginate anti-reflection layer (32) are independently 120-200 nm; Preferably, the first inorganic fluorine compound-alginate anti-reflection layer (31) and the second inorganic fluorine compound-alginate anti-reflection layer (32) have the same thickness.

6. The method for preparing photovoltaic glass according to any one of claims 1 to 5, characterized in that: The following steps are involved: The silica-alginate coating liquid and the alumina-alginate coating liquid are applied to the surface of the glass body (1) in an arbitrary order.

7. The preparation method according to claim 6, characterized in that: sequentially coating the silica-alginate coating liquid and the alumina-alginate coating liquid onto the surface of the glass body (1); Preferably, the alginate is sodium alginate and / or potassium alginate.

8. The preparation method according to claim 6, characterized in that: The method comprises the following steps: sequentially coating a first inorganic fluorine compound-alginate coating liquid, the silicon dioxide-alginate coating liquid, the aluminum oxide-alginate coating liquid, and a second inorganic fluorine compound-alginate coating liquid on the surface of the glass body (1); Preferably, the inorganic fluorine compound is selected from at least one of magnesium fluoride, sodium fluoride, potassium fluoride and calcium fluoride, preferably magnesium fluoride; Preferably, the coating is performed by dipping; the coating conditions at least include: an ultrasonic frequency of 50-200 Hz, a temperature of 40-60° C., a rotation speed of 200-300 rpm, and a time of 20-100 min; Preferably, the coating time of the first inorganic fluorine compound-alginate coating liquid and the coating time of the second inorganic fluorine compound-alginate coating liquid are the same.

9. The preparation method according to claim 8, characterized in that: The silica-alginate coating liquid, the alumina-alginate coating liquid, the first inorganic fluorine compound-alginate and the second inorganic fluorine compound-alginate coating liquid each independently further contain a crosslinking agent, and the crosslinking agent is selected from at least one of epichlorohydrin, boric acid and ethylene glycol diglycidyl ether; Preferably, the concentration of silica in the silica-alginate coating liquid is 20-50 g / L, and the weight ratio of silica to alginate is 1:0.6-1.5; the concentration of alumina in the alumina-alginate coating liquid is 15-25 g / L, and the weight ratio of alumina to alginate is 1:1.5-3; the concentrations of inorganic fluorine compounds in the first inorganic fluorine compound-alginate coating liquid and the second inorganic fluorine compound-alginate coating liquid are each independently 40-60 g / L, and the weight ratios of inorganic fluorine compounds to alginate are each independently 1:0.6-1.

10. Use of the photovoltaic glass described in any one of claims 1 to 5 or the photovoltaic glass obtained by the preparation method described in any one of claims 6 to 9 in solar cells.